2020
DOI: 10.1620/tjem.250.79
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Pain Is Associated with Lower Back Pain among Young Basketball Players: A Cross-Sectional Study

Abstract: Basketball is a major sport worldwide among different age groups that leads to a high frequency of injuries at multiple body sites. Upper and lower extremities and lower back are common pain sites in basketball players; however, there is little information about the relationship between upper or lower extremity pain and lower back pain. This study elucidated the associations between upper extremity (shoulder and elbow) pain and lower back pain (LBP) among young basketball players. We conducted a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…In the process of setting up the principle model of the goal system of basketball players, the action point of the joint force when the ball is thrown is calculated, the action point of the joint force transmitted by the femoral head of the human body is shifted outward, the stress distribution curve of the femur under the action of the force on the femoral head is obtained, and the principal model of the goal system of basketball players is established [13,14]. e specific steps are described as follows:…”
Section: Principle Model Of Goal System For Basketball Playersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of setting up the principle model of the goal system of basketball players, the action point of the joint force when the ball is thrown is calculated, the action point of the joint force transmitted by the femoral head of the human body is shifted outward, the stress distribution curve of the femur under the action of the force on the femoral head is obtained, and the principal model of the goal system of basketball players is established [13,14]. e specific steps are described as follows:…”
Section: Principle Model Of Goal System For Basketball Playersmentioning
confidence: 99%
“…In formula (13), ε represents the regularization parameter, w represents the number of classifiers, f represents the training function, x i and y i represent the independent and dependent variables of the function, and i represents the training times. To prevent fitting in the classifier training process, the optimal solution of the aforementioned calculation formula ( 13) is taken, and the calculation formula of the optimal solution can be expressed in the following equation:…”
Section: Build Team Strength Evaluation Algorithmmentioning
confidence: 99%
“…Previous systematic reviews have reported that the prevalence of LBP in these athletes ranges from 17% to 94% [1,2]. Specifically, the prevalence of LBP in past 12 months has been reported from 6.5% to 47% in soccer players [3][4][5] and from 12.8% to 44% in basketball players [6][7][8]. A previous episode of LBP is often predictive of future back injury [9], which will affect sports participation and performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] According to a study of 590 basketball athletes, 12.9% reported low back pain. 10 In many cases, pain can even prevent subjects from performing daily activities. 1 In elite basketball players aged 13-19 years, the prevalence of back pain (49% vs. 28%) and neck pain (42% vs. 20%) is higher in women than men.…”
Section: Introductionmentioning
confidence: 99%